Crisis management of the economy of Kazakhstan in conditions of turbulence of the environment (Journal of Economic Research & Business Administration, 2016)
The article discusses the features of anti-crisis management of the economy of Kazakhstan in conditions of turbulence of the environment. As highlighted in the important factors such as socially responsible business, the rate of return on investment, the competence approach. The importance of developing a model of strategic management in the conditions of turbulence due to the change of priorities of society, does not require quantitative and qualitative characteristics of the standard of living. The business structure gets its direction of development is not only and not so much under the influence of the internal control system, but to a greater extent under the influence of the environment, which in conditions of financial crisis it is more expedient to call turbosredoy. This environment makes the linear process in a turbulent, flowing with a lot of probability trajectories of development. Today, the domestic economy is once again entering a period of economic turbulence, and thus once again become relevant issues of crisis management, its methodological and instrumental development. At the same time, rising in the question of the anti-crisis restructuring as a concept in theory and practice both for individual organizations.
Keywords: anticrisis; management; economics; the turbulence of the environment; the rate of return on investment; business structure; strategic management; turbulence.